Horizontal Dynamic Resource Scaling on Scheduling Interval in multi-tenant Cloud Computing - Aaqib Rashid , Fayaz Ahmad Lone, Amit Kr. Chaturvedi (International Journal of Advanced Science and Technology, 2020)
Cloud computing provides multiple computing resources to its multiple users on sharing basis. The processing load of the multiple clients may increase or decrease and hence the requirement of computing resources as well. This unpredictable change in the resource requirement is called resource scaling or elasticity. When this resource scaling is done on runtime then it is called dynamic resource scaling and it may be done automatically after a specified time and is called scheduling interval or rapidness. The dynamic resource scaling may be done horizontally or vertically. In Horizontal dynamic scaling the particular server will be equipped with capable resources to serve the requirement in a better way, whereas in Vertical dynamic Scaling the number of servers are increased while increase in resource requirements. So, analysing our simulation setup for rapid elasticity on horizontal dynamic resource scaling is the main objective of writing this research paper.